FOXE1 supports the tumor promotion of Gli2 on papillary thyroid carcinoma by the Wnt/β‐catenin pathway. Issue 10 (22nd February 2019) - Ma, Jiancang; Huang, Xin; Li, Zongyu; Shen, Yawei; Lai, Jingyue; Su, Qinghua; Zhao, Jun; Xu, Jinkai
Abstract: Papillary thyroid carcinoma (PTC) is a common malignancy in thyroid tissue. However, the molecular mechanism of PTC tumor progression remains unknown. The hedgehog (Hh) pathway is thought to play a key role during PTC development. Here we investigate the effects of glioma‐associated oncogene protein‐2 (Gli2), an important transcription factor of the Hh‐signaling pathway, on PTC. Gli2 and forkhead box E1 (FOXE1) protein levels were upregulated in tissues of PTC patients and PTC cell lines. Using the PTC cell line TPC‐1, we show that Gli2 small interfering RNA (siRNA) reduces cell proliferation, migration, and invasion; whereas overexpression of FOXE1 produces the opposite effects. Moreover, Gli2 siRNA inhibited the expression of genes implicated in the Wnt/β‐catenin pathway and that FOXE1 overexpression produces the opposite effects. Thus, it was indicated that Gli2 promoted the proliferation, migration, and invasion of TPC‐1 cells by activating Wnt/β‐catenin and FOXE1 is involved in this process. Xenograft models of PTC were also constructed, the results showed that Gli2 siRNA reduced the rate of tumor growth, FOXE1 levels, and the expression of the Wnt/β‐catenin pathway but FOXE1 overexpression reversed that effects. In conclusion, this study demonstrates that Gli2 promotes the growth of PTC tumors and TPC‐1 cell proliferation, migration, and invasion by activating the Wnt/β‐catenin pathway via FOXE1. Abstract : Altogether, this evidence provides valuable insights into the role of glioma‐associated oncogene protein‐2 (Gli2) in carcinogenesis and tumor progression of papillary thyroid carcinoma. Knowledge of the Gli2‐FOXE1‐Wnt/β‐catenin crosstalk may also help to identify potential new targets for therapy.